2020
DOI: 10.1136/postgradmedj-2020-137706
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome (PRES): presentation, diagnosis and treatment

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a neurological disorder which is characterised by variable symptoms, which include visual disturbances, headache, vomiting, seizures and altered consciousness. The exact pathophysiology of PRES has not been completely explained, but hypertension and endothelial injury seem to be almost always present. Vasoconstriction resulting in vasogenic and cytotoxic edema is suspected to be responsible for the clinical symptoms as well as the neuro-radiological presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
0
45
1
2
Order By: Relevance
“…Till now, the pathomechanism underlying PRES is yet to be thoroughly elucidated. Two competing theories have been proposed, both of which entail disruption of the blood-brain barrier and fluid leakage into the interstitial tissues, leading to the edematous change of cerebral parenchyma (9,15,16). However, more evidence indicates that vasogenic edema rather than cytotoxic edema plays a more critical role in the pathogenesis of PRES (17,18).…”
Section: Potential Pathomechanisms Of Presmentioning
confidence: 99%
See 3 more Smart Citations
“…Till now, the pathomechanism underlying PRES is yet to be thoroughly elucidated. Two competing theories have been proposed, both of which entail disruption of the blood-brain barrier and fluid leakage into the interstitial tissues, leading to the edematous change of cerebral parenchyma (9,15,16). However, more evidence indicates that vasogenic edema rather than cytotoxic edema plays a more critical role in the pathogenesis of PRES (17,18).…”
Section: Potential Pathomechanisms Of Presmentioning
confidence: 99%
“…Nevertheless, patients with PRES always require management in the setting of intensive care units given that hypertensive crisis, status epilepticus, coma, or respiratory failure may complicate PRES, which require aggressive interventions (7,15,18). In adult medicine, it has been suggested that the management of PRES should be better delivered in a neurocritical care setting with meticulous neurological monitoring and interventions (9,16,46). However, besides neurological specialty, it usually requires frequent consultations with other specialties, including hematologist-oncologist, nephrologists, rheumatologists, or obstetricians, according to the diverse underlying comorbidities (31).…”
Section: Monitoring and Management Of Pres In Pediatric Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…The common presenting complaints include seizures, headache, visual disturbances, and altered sensorium [ 6 , 7 ]. Diffusion-weighted MRI is the imaging modality of choice for confirming the presence of typical or atypical radiographic features [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%